1977
DOI: 10.1007/bf01964886
|View full text |Cite
|
Sign up to set email alerts
|

Determination of histaminase (diamine oxidase) activity byo-dianisidine test: Interference of ceruloplasmin

Abstract: Until now o-dianisidine was used as an indicator substance in a test system for the determination of diamine oxidase. More recently, however, this substance was also used to measure ceruloplasmin activity. A study of the test principles revealed that o-dianisidine was the one denominator for both enzymes. As it was found for diamine oxidase the indicator was oxidized via peroxidase mediated H2O2 cleavage. Ceruloplasmin, however, oxidized o-dianisidine directly with resulting free radical formation. An addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In vivo, the most likely physiological amine substrates are dopamine, 5-OH tryptamine (serotonin), epinephrine and nor-epinephrine, 50 but not histamine (although histamine does bind). 6,51 These amines are hormones or hormone precursors, and oxidation would result in their inactivation. As all hormone signals must be rapidly eliminated to prevent prolonged unregulated effects, it seems likely that Cp contributes to the inactivation of these natural bioactive amines.…”
Section: Small Hormone Oxidation By Cpmentioning
confidence: 99%
“…In vivo, the most likely physiological amine substrates are dopamine, 5-OH tryptamine (serotonin), epinephrine and nor-epinephrine, 50 but not histamine (although histamine does bind). 6,51 These amines are hormones or hormone precursors, and oxidation would result in their inactivation. As all hormone signals must be rapidly eliminated to prevent prolonged unregulated effects, it seems likely that Cp contributes to the inactivation of these natural bioactive amines.…”
Section: Small Hormone Oxidation By Cpmentioning
confidence: 99%
“…BmGAr~SKI et al found an increase of plasma ceruloplasmin oxidase activity during experimental inflammation in guinea-pigs [18]. SCUDDER et al showed an increase of both ceruloplasmin (immunologically determined) and copper concentrations in the serum of rheumatoid patients and described the existence of a strong positive correlation between the two parameters [14].…”
Section: Introductionmentioning
confidence: 96%
“…Also in experimental models of inflammation an increase of serum copper concentration was repeatedly described as characteristic, regardless of the irritant and the animal species used. In particular, a rise of serum copper was measured after the injection of turpentine oil in rats [17], guinea-pigs [18], dogs [19] and rabbits [20] and after the injection of carrageenan [21] or Mycobacterium butyricum, suspended in liquid paraffin [22], in the rat.…”
Section: Introductionmentioning
confidence: 99%